Everything, everywhere, all at once: A study of polychronicity, work-school facilitation, and emotional exhaustion in working students - Grogan, Allan; Lilly, Juliana (Frontiers in Psychology, 2023)
This study investigates how a preference for multitasking serves as a resource towards mitigating emotional exhaustion through the mediating role of work-school facilitation. Utilizing conservation of resources (COR) theory, we utilized a sample of 153 working students in a time-lagged study to examine the relationship between these variables. Results suggest that polychronicity serves as a valuable resource toward balancing the simultaneous needs of work and school, and ultimately, decreasing academic emotional exhaustion. The findings presented in this study further advance scholarship in this domain by highlighting our understanding of polychronicity as an individual difference variable in facilitating role balance within the school-work domain. Practical implications and limitations are discussed.